Unveiling the Delphi method: an in-depth introduction - Ting, Hie-Ling (Corporate Communication Unit, UiTM Mukah Campus, 2022)
The Delphi method is a structured process through which experts share opinions and reach agreement on complex topics. Dr. Leow described it as a “structured group discussion” done in multiple rounds. For example, experts answer questions anonymously, discuss results, and revise their answers until common ground is achieved. This method is widely used in fields such as business, healthcare, and education for balanced decision-making.